Feasibility of blood speckle imaging parameters as predictors of intracavitary thrombus in apical aneurysm. (4th February 2022) - Montes, A; Cecconi, A; Martinez Vives, P; De Rueda, C; Gamarra, A; Perich, J; Roquero, P; Martinez Avial, M; Rojas, AM; Lopez Melgar, B; Diego, G; Benedicto, A; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: In patients with apical aneurysm, left ventricular thrombus (LVT) is a major complication associated with systemic embolism. Likely, abnormalities in apical wall contraction produce stagnant flow which leads to the thrombus formation. Currently, there is a lack of knowledge about predictors of thrombus in such patients. However, new imaging techniques might be able to identify flow properties useful for risk stratification. Specifically, blood speckle imaging (BSI), a technology based on high-frame rate ultrasound, is a promising pattern-matching technique that could allow a comprehensive assessment of blood flow in patients with apical aneurysms (1, 2). Purpose: The aim of the study was to demonstrate the feasibility of obtaining quantitative and qualitative measurements with BSI in patients with apical aneurysms and to explore which parameters may be associated with LVT. Methods: We examined cases of patients with apical aneurysm and LVT studied in our tertiary center. In order to exclude from our analysis the pro-inflammatory effects of the acute event, patients with thrombus formation within the first month after the ischemic event were excluded. Patients with current presence of thrombus were also discarded. A control group of patients with apical aneurysm but without history of LVT was included. A basic 2-dimensional echocardiography study was obtained, along with BSI images. BSI acquisitions were performed with a 29 cm/s (2.5 mHz) scale. Data regarding vortex flow were collected, including its presence, area, length, besides area without BSI vectors (Image 1). All measures were indexed by telediastolic left ventricular volume. Results: Eight patients with apical aneurysms were enrolled in the study, four of them with history of LVT. Although in patients with history of thrombus a larger vortex area was found  (Table 1), none of the differences in the BSI parameters was statistically significant. Conclusion: This study shows for the first time the feasibility of BSI for characterizing complex flow patterns such as vortex in patients with apical aneurysms. Explorations in larger cohorts of patients are needed to prove significant findings with this technology in the future.